2016
DOI: 10.2147/ijn.s112045
|View full text |Cite
|
Sign up to set email alerts
|

Optimization, formulation, and characterization of multiflavonoids-loaded flavanosome by bulk or sequential technique

Abstract: This study involves adaptation of bulk or sequential technique to load multiple flavonoids in a single phytosome, which can be termed as “flavonosome”. Three widely established and therapeutically valuable flavonoids, such as quercetin (Q), kaempferol (K), and apigenin (A), were quantified in the ethyl acetate fraction of Moringa oleifera leaves extract and were commercially obtained and incorporated in a single flavonosome (QKA–phosphatidylcholine) through four different methods of synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…In comparison with the other spectra, marked changes were observed in EAPC, which confirmed the successful formation of Fungisome. The results were in accordance with the IR spectra of previously reported phytosomes (Karthivashan et al., 2016; El‐Fattah et al., 2017; Rathee & Kamboj, 2018; Telange et al., 2017).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In comparison with the other spectra, marked changes were observed in EAPC, which confirmed the successful formation of Fungisome. The results were in accordance with the IR spectra of previously reported phytosomes (Karthivashan et al., 2016; El‐Fattah et al., 2017; Rathee & Kamboj, 2018; Telange et al., 2017).…”
Section: Resultssupporting
confidence: 92%
“…In this study, the ς potential value of EAPC comes under ±40 to ±60 mV colloid stability, which indicates the good stability condition (Mahajan & Ramana, 2014). Liposome that possess zeta potential <−30 mV are considered as the optimum formulation (Hadian, Sahari, Moghimi, & Barzegar, 2014; Karthivashan et al., 2016). Generally, the suspensions with high ς potential values, either positive or negative were electrically stable due to the high electrostatic repulsion forces among the particles whereas the low ς potential values tend to coagulate/aggregate results in poor stability (Hadian et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After checking for many physicochemical properties, they suggested that this three-in-one flavonosome with sustained activity is a good candidate as an antioxidant, hepatoprotective, and heat supplement agent. 169 More examples of herbal loaded NE are presented in Table 1. [170][171][172][173][174][175] Self Nanoemulsifying Drug Delivery System (SNEDDS) SNEDDS is a lipid-based anhydrous isotropic mixture of oil, surfactant(s) and cosurfactant(s) with a particle size of 20-200 nm ( Figure 11).…”
Section: Micellementioning
confidence: 99%